19th International Scientific Conference Engineering for Rural Development Proceedings 2020
DOI: 10.22616/erdev.2020.19.tf012
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring possibility of functioning of tractors in agricultural production taking into account residual resources of their units and systems

Abstract: Annotation. Development of agriculture in the conditions of market relations is accompanied by aggravation of the problem of efficiency of use of machinery. In this connection, the task of scientists is to increase the actual volume of work performed by tractor units, reducing the cost per unit of production. The high cost of tractors, lack of personnel, reduction of technical equipment of farms and the increase in the volume of products produced in the agro-industrial complex, natural and climatic conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 5 publications
(2 reference statements)
0
10
0
4
Order By: Relevance
“…As a result of the research, it was found that the number of failures increases with increasing wear and tear of equipment, which will eventually lead to an increase in the recovery period [2]. In this regard, research aimed at ensuring the performance of systems and units, as well as tractors and agricultural machines in general, is relevant.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the research, it was found that the number of failures increases with increasing wear and tear of equipment, which will eventually lead to an increase in the recovery period [2]. In this regard, research aimed at ensuring the performance of systems and units, as well as tractors and agricultural machines in general, is relevant.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the processes occurring in the soil under the influence of the working body depends on its geometric parameters, operating modes and physical and mechanical properties of the soil. The shape of the working body mainly determines the quality of tillage and its energy consumption [1][2][3][4][5][6]. Academician V.P.…”
Section: Introductionmentioning
confidence: 99%
“…Еще один важный фактор, связанный с плодородием почвы, -устойчивость почвенных агрегатов (WSA), которая определяет способность сопротивления почвы разрушающему воздействию осадков, стокаповерхностных вод и ветра. Помимо внешних факторов, на величину этого показателя влияют многие внутренние свойства почвы, например, содержание органических веществ, гранулометрический состав, пористость и др., а также эффективность управления землепользованием [7].…”
unclassified